Effect of reduced doses of mesosulfuron + iodosulfuron to control weeds in no-till wheat under Mediterranean conditions - Barros, José (2009)
Field experiments were carried out over three years (2004-05, to 2006-07) to study the efficacy of a post-emergence dual-purpose herbicide (mesosulfuron – methyl (3%) + iodosulfuron – methyl – sodium (0.6%) + mefenpyr – diethyl (9%) to control Lolium rigidum Gaud. and broad-leaved weeds in no-till wheat (Triticum aestivum L.). A ready herbicide mixture was used at three doses (6+1.2, 9+1.8 and 12+2.4 g a.i. ha–1) on two dates (beginning of tillering for L. rigidum and 2-3 pair of leaves for broad-leaved weeds, and complete tillering for L. rigidum and 5-6 pair of leaves for broad-leaved weeds) with three different application volumes (100, 200 and 300 L ha–1). The results of the present study reveal that using lower than the recommended dose (12+2.4 g ha–1), the herbicide mixture controls L. rigidum better than it controls some broad-leaved weeds. Effective weed control, which was achieved mainly through the application at the first weed development stage, provided higher grain yields. The lower control efficacy of more developed L. rigidum and broad-leaved weeds and a longer period of competition between crop and weeds are responsible for the significantly lower crop yields for the delayed application. Within each application timing significant differences were obtained among the dose/volume combinations, with the exception of the first application regarding L. rigidum control, indicating that a reduction in herbicide dose is possible, but only for certain dose/volume combinations. Nonetheless, weed control was maintained across an array of dose/volume combinations, especially with L. rigidum, thus, our results demonstrate that reduced doses can effectively control weeds if applied early.